2020
DOI: 10.3389/fimmu.2020.01997
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Driven Deficiencies of Specialized Pro-resolving Mediators May Drive Adverse Outcomes During SARS-CoV-2 Infection

Abstract: Obesity is a major independent risk factor for increased morbidity and mortality upon infection with Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2), which is responsible for the current coronavirus disease pandemic (COVID-19). Therefore, there is a critical need to identify underlying metabolic factors associated with obesity that could be contributing toward increased susceptibility to SARS-CoV-2 in this vulnerable population. Here, we focus on the critical role of potent endogenous lipid metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…Studies in mice models of acute infection have found that a high dietary intake of ω3-PUFAs significantly reduces IFN-gamma secretion ( 16 ). In fact, it has been hypothesized that some of the increased susceptibility of individuals with obesity to adverse outcomes after SARS-CoV-2 infection may be a consequence of their relative deficiency of SPMs derived from ω3-PUFAs ( 17 ). Furthermore, a recent proof-of-concept randomized trial in 100 patients with symptomatic COVID disease evaluated the effect of supplementation with icosapent ethyl, a highly purified preparation of EPA, on inflammation and symptomatology over 14 days.…”
Section: Nutrients With Immunomodulatory Properties Present In Fishmentioning
confidence: 99%
“…Studies in mice models of acute infection have found that a high dietary intake of ω3-PUFAs significantly reduces IFN-gamma secretion ( 16 ). In fact, it has been hypothesized that some of the increased susceptibility of individuals with obesity to adverse outcomes after SARS-CoV-2 infection may be a consequence of their relative deficiency of SPMs derived from ω3-PUFAs ( 17 ). Furthermore, a recent proof-of-concept randomized trial in 100 patients with symptomatic COVID disease evaluated the effect of supplementation with icosapent ethyl, a highly purified preparation of EPA, on inflammation and symptomatology over 14 days.…”
Section: Nutrients With Immunomodulatory Properties Present In Fishmentioning
confidence: 99%
“…Obesity is a risk factor for SARS-CoV-2 infection, and a BMI of 30 kg/m 2 increases the risk of infection by 61% (Bello-Chavolla et al 2020 ). This is likely due to a deficiency of SPMs in obese patients, and this deficiency promotes adverse reactions during SARS-CoV-2 infection (Pal et al 2020 ). LXA4, Elovanoid-N32 or RvD6 isomers reduced expression of angiotensin-converting enzyme 2 (ACE2), but NDP1 did not reduce it.…”
Section: Role Of Spms and Their Receptors In Virus Infectionsmentioning
confidence: 99%
“…coli as well as regulate leukocyte transcripts of interest in infections. Hence, the nutritional availability of dietary n-3 PUFA and marine oils enriched with the SPM intermediate precursors (e.g., 17-HDHA, 18HEPE), along with increasing local biosynthesis of SPMs [ 26 ] to functional concentrations maybe an approach of value during Covid-19 as well as in prevention and shortening their recovery phase from infections.…”
Section: Evolutionary Aspects Of Diet and N-6 Pufa And N-3 Pufa Biosymentioning
confidence: 99%
“…In today’s diet 72% of calories come from foods that were not present during evolution [ 8 ]. In the meantime, physicians should consider measuring PUFAs and their potent cellular effectors both the eicosanoids and SPMs, in patients with Covid-19 and in patients with chronic diseases as in refs [ 24 , 25 , 26 , 28 ], specifically obesity, type 2 diabetes, hypertension and CHD by measuring LA, ALA, and the LA/ALA ratio, ARA+EPA+DHA and ARA/EPA+DHA ratio in red blood cell membrane phospholipids (RBC’s) and aim for balance in the dietary intake of n-6 and n-3 PUFA. FDA should not continue to list PUFA on the food label and should replace the term “PUFA” with actual amounts of the individual molecules namely LA, ALA, ARA, EPA and DHA, and eventually industry should adopt an n-6/n-3 “ratio” per serving in all processed foods [ 34 ].…”
Section: Evolutionary Aspects Of Diet and N-6 Pufa And N-3 Pufa Biosymentioning
confidence: 99%